Application and evaluation of whole-process nursing in venous thromboembolism patients - Diao, Yaqian; Huang, Yu; Cui, Xue; Ma, Xinhua; Zhao, Hanxiao; Chen, Muxi; Zhao, Zhuzhu; Gao, Ruijiao (Frontiers in Public Health, 2025)
BackgroundVenous thromboembolism (VTE) is a serious threat to patient health. Currently, its management faces the problems of lack of patient awareness, poor medical and nursing management, and lack of out-of-hospital management. The traditional care model is difficult to meet the demand, and the whole process care management model (WPCM) has become an important direction of research to optimise the care of VTE patients.ObjectiveTo evaluate the effectiveness of this model in patients with VTE and provide a basis for standardised management.MethodsA total of 1,392 patients admitted to our hospital from March 2023 to December 2024 with thrombosis due to filter placement were divided into an experimental group and a control group according to the time of admission. The experimental group adopted the WPCM, and the control group received routine care. Comparison of psychosomatic status, quality of life, standardised anticoagulation, filter removal, complications, hospital stay and patient satisfaction during hospitalisation in both groups.ResultsThere were no significant differences between the two groups in terms of baseline data such as gender, age, BMI and some indicators, p > 0.05. However, the experimental group had lower intrafilter thrombosis, incidence of PTS, length of hospital stay, average hospital costs and higher patient satisfaction than the control group, p < 0.05.ConclusionThe whole process management nursing mode is of great benefit to patients with venous thromboembolism. It can effectively reduce the incidence of in-filter thrombosis and PTS (post-thrombotic syndrome), shorten hospital stays, reduce costs and improve patient satisfaction, making it worthy of widespread clinical application.